THE QURAN'S RESPONSE TO DOMESTIC VIOLENCE - Abdul Aziz, Umair (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study examines domestic violence and explores how the Qur’an responds to such acts. It presents an analytical conclusion based on applied theoretical frameworks, revealing that domestic violence has persisted throughout history and continues to this day. This research adopts a library research approach by collecting and analyzing qualitative data from both primary and secondary sources relevant to the theme. The primary focus of this study is the Qur’anic response to domestic violence. A key finding of this study, viewed through a historical lens, is that domestic violence has long existed—initially in societies where victims were marginalized and lacked social standing—until the arrival of Islam, which acknowledged their dignity and provided them with protection. However, even today, misinterpretations of divine revelation still occur, often placing victims in unfavorable positions. The author considers this study crucial for further exploration, emphasizing the need for reinterpreting related Qur’anic verses to reinforce Islam as a religion that is shâlih li kulli zamân wa al-makân (relevant for all times and places)